PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP KEPUASAN KONSUMEN MELALUI KUALITAS PELAYANAN PERUMAHAN METRO CILEGON / PT. PERDANA GAPURA PRIMA - Nurhayani Nurhayani (Universitas Serang Raya, 2017)
his study arises from the competition between companies similar housing in the city of Cilegon which resulted in a decrease in the number of sales of housing units. The purpose of this study was to determine and analyze the influence of the marketing mix (Marketing Mix) on customer satisfaction through service quality Perum Metro Cilegon / PT. Prime Gapura Prima. The population was Perum Metro Cilegon residents being occupied by theconsumer or PT Perum Metro Cilegon. Prime Gapura Prima at the time this study was conducted. Method of determining the sample is purposive sampling of 180 people. The research instrument was a questionnaire contains questions that are answered respondents.Research analysis method using SEM (Structural Equation Model) that is run by an AMOS software. Results of the analysis showed that the mix of marketing (Marketing Mix) significantly affects customer satisfaction through quality of service. These findingsindicate that the marketing mix significantly influence the quality of service to the value of CR for 3.472, the service quality significantly influence consumer satisfaction with the value of CR for 2.242 and the marketing mix does not significantly influence consumer satisfaction with CR value of 0.923.